Political change and consolidation : democracy's rocky road in Thailand, Indonesia, South Korea, and Malaysia - Freedman, Amy L. (Palgrave Macmillan, 2006)
In the immediate aftermath of the 1997-98 Asian financial crisis, several countries went through political transformations. Indonesia, South Korea, and Thailand all underwent political reform and democratization. Malaysia, although also hit by the financial crisis, remained authoritarian. Is there a connection between economic crises and political change? Once the crisis abates do changes stick? Why did political reform happen in some places and not in Malaysia? Several factors are useful in explaining the variation in political transitions: IMF involvement, popular protests, the nature of political opposition, and elite alliances at the highest levels of government all help determine the success or failure of democratization efforts.